UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 4-5 TAHUN MELALUI MEDIA STIK WARNA - Tiara Safitri, Habib Cahyono, Yayah Rukiyah (Jurnal Pendidikan dan Penelitian Semesta Mendidik, 2024)
This study aims (1) to find out if there is an improvement in cognitive abilities through color media in children aged 4-5 years in PAUD Bunda Pertiwi Prefecture of Tanara. (2) To find out how the color media can enhance cognitive abilities in kids aged 4 - 5 years in Paud Bunda Partiwi prefecture.This research is Class Action Research. The classroom action research (PTK) in English is often called Classroom Action Research. The study was conducted in May 2024 with children aged 4-5 years of age, consisting of 15 children, 9 boys, 5 girls. The study of class action is carried out over two cycles namely cycle I and cycle II. Data collection methods are performed by oral tests, observations, interviews and documentation. Data analysis uses data collection, data reduction, data presentation and conclusion drawings.The improvement in the cognitive ability of the child can be seen from the initial condition (pre-cycle), cycle and cycle II. In the early condition the presentation of the improvement of the cognitive ability of a child with the category developing according to expectation (BSH) and developing very well (BSB) was at a presentation of 6.67% or 1 child. In cycle I, the increase in the cognitive capacity of the kid was increased to 46.67%, or 7 children.